2011
DOI: 10.1002/jat.1778
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose probenecid selectively inhibits urinary excretion of phenolsulfonphthalein in rats without affecting biliary excretion

Abstract: Renal organic anion transport systems play an important role in the excretion of anionic drugs and toxic compounds. Probenecid has been used as a potent inhibitor of urinary and biliary excretion of anionic compounds mediated by transporters such as organic anion transporters and multidrug resistance-associated protein 2 (Mrp2). The purpose of this study was to optimize the dose of probenecid required for selective inhibition of urinary excretion of anionic compounds in rats, without inhibition of biliary excr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The presence of oat transporters in the kidney, as well as on the basolateral side of the BBB combined with a lack of specificity of oat inhibitor probenecid preclude a targeted brain augmentation of bumetanide. [40,[55][56][57] However, the other possible targets of probenecid which are present at the BBB, including organic anion-transporting polypeptide 1a4 and multidrug resistance protein transporters, have not previously been shown to have any influence on bumetanide transport. [30,58] Also, the basolateral location of oat3 on the BBB makes for a more difficult drug target, as the inhibitor must cross through the apical side of the BBB to reach it.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of oat transporters in the kidney, as well as on the basolateral side of the BBB combined with a lack of specificity of oat inhibitor probenecid preclude a targeted brain augmentation of bumetanide. [40,[55][56][57] However, the other possible targets of probenecid which are present at the BBB, including organic anion-transporting polypeptide 1a4 and multidrug resistance protein transporters, have not previously been shown to have any influence on bumetanide transport. [30,58] Also, the basolateral location of oat3 on the BBB makes for a more difficult drug target, as the inhibitor must cross through the apical side of the BBB to reach it.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the protein expression of Mrp2 in the hepatic plasma membrane fractions of HL rats significantly decreased (by 24.3%) compared with that of the control rats (Figure ). This reduced expression of hepatic Mrp2 in HL rats resulted in a significantly smaller (by 24.6%) 6 h cumulative biliary excretion of PSP, which is a model anion substrate for Mrp2 , relative to the control rats (Figure A). The comparable bile flow rates of the two groups (Figure B) suggested that the decreased biliary excretion in HL rats was not due to reduced bile flow.…”
Section: Discussionmentioning
confidence: 96%
“…The present study evaluated changes in the expression levels and activity of hepatic Mrp2 in a well‐established rat model of hyperlipidemia induced by poloxamer 407 [8−10]. Phenolsulfonphthalein (PSP) was used as a model anion substrate for Mrp2, which mediates its biliary excretion in rats . Additionally, we also examined changes in the pharmacokinetics of MPA and MPAG after the intravenous or oral administration of MPA, as well as changes in the hepatic metabolic activity of MPA to MPAG and the plasma protein binding of these compounds in the rat model of hyperlipidemia.…”
Section: Introductionmentioning
confidence: 99%
“…It will be of major importance to dissect the effects of PBN and to elucidate its molecular targets in the context of EAE. Although PBN clearly inhibits Panx1 channel activity 7 , its direct inhibitory effects on the purinergic P2X7 receptor 17 and the inhibition of organic anion transporters 18 also have to be taken into account. Interestingly, application of various pharmacologic inhibitors in EAE consolidate the importance of the Panx1 – P2X7 axis in the pathology of demyelinating conditions: Inhibition of P2X7 19 , pharmacologic inhibition via carbenoxolone or mefloquine – both of which inhibit connexin and pannexin channels 3 , 20 , 21 –, as well as Panx1 deficiency in mice 3 , all prevent or delay the onset of EAE.…”
Section: Discussionmentioning
confidence: 99%